Targeting hypoxia signaling pathways in angiogenesis - Monaci, Sara; Coppola, Federica; Filippi, Irene; Falsini, Alessandro; Carraro, Fabio; Naldini, Antonella (Frontiers in Physiology, 2024)
Oxygen (O2) supply is constantly maintained by the vascular network for a proper tissue oxygenation.Hypoxia is the result of an increased O2 demand and/or decreased supply and is common in both physiological conditions and human diseases. Angiogenesis is one of the adaptive responses to hypoxia and is mainly regulated by the hypoxia-inducible factors, HIFs. These heterodimeric transcription factors are composed of one of three O2-dependent α subunits (HIF-1, HIF-2, and HIF-3) and a constitutively expressed O2-insensitive subunit (HIF-1β). Among them HIF-1α is the most characterized and its activity is tightly controlled. Under hypoxia, its intracellular accumulation triggers the transcription of several genes, involved in cell survival/proliferation, autophagy, apoptosis, cell metabolism, and angiogenesis. HIF pathway is also modulated by specific microRNAs (miRNAs), thus resulting in the variation of several cellular responses, including alteration of the angiogenic process.The pro-angiogenic activity of HIF-1α is not restricted to endothelial cells, as it also affects the behavior of other cell types, including tumor and inflammatory/immune cells. In this context, exosomes play a crucial role in cell-cell communication by transferring bio-active cargos such as mRNAs, miRNAs, and proteins (e.g., VEGFA mRNA, miR210, HIF-1α). This minireview will provide a synopsis of the multiple factors able to modulate hypoxia-induced angiogenesis especially in the tumor microenvironment context. Targeting hypoxia signaling pathways by up-to-date approaches may be relevant in the design of therapeutic strategies in those pathologies where angiogenesis is dysregulated.